The role of tor signaling in the mechanisms of adaptation of Arabidopsis thaliana to salt stress (Experimental biology, 2015)
TOR (target of rapamycin) kinase is present in most species of higher eukaryotes and plays a key role in the regulation of growth and development of organisms and the formation of the metabolic response of the cell to the action of various stress factors. However, despite the importance TOR signaling in eukaryotes, the physiological mechanisms involving the regulation of this enzyme in plants are still poorly understood. In this paper, was examined the role of TOR kinase in the physiologica mechanisms of adaptation of Arabidopsis thaliana to salt stress by using a mutant line in AtTOR gene. It was found increased activity of aldehyde oxidase and xanthine dehydrogenase in mutant line under salt stress. Based on activity of these enzymesparticipating in ABA biosynthesis we suggest that TOR kinase can act as a negative factor of ABA biosynthesis regulation under certain conditions
Keywords: Arabidopsis thaliana; TOR; aldehyde oxidase; xanthine dehydrogenase; ABA; salt stress